Is it necessary for young patients with recurrent implantation failure to undergo preimplantation genetic testing for aneuploidy? - Du, Yulin; Guan, Yichun; Li, Na; Shi, Congxing; Zhang, Yongjie; Ren, Bingnan; Liu, Jing; Lou, Hua (Frontiers in Endocrinology, 2023)
ABSTRACT Objective: To determine whether preimplantation genetic testing for aneuploidy (PGT-A) can improve the pregnancy outcomes of patients aged under 38 years who have a history of recurrent implantation failure(RIF). Design: Retrospective cohort study. Methods: We retrospectively studied the pregnancy outcomes of RIF patients aged under 38 years from January 2017 to December 2021.178 patients were divided into two groups according to whether they underwent PGT-A: the PGT-A group(n=59)and the control group(n=119).In the PGT-A group,we compared the euploidy rate of the different quality and developmental rate blastocysts. In both groups,the patients were the first frozen-thaw single blastocysts transfer after the diagnosis of RIF.Among the pregnancy outcomes, the clinical pregnancy rate was assessed as the primary outcome.The spontaneous abortion rate and ongoing pregnancy rate were the secondry outcomes.The generalized estimation equation was used to adjust for the blastocysts derived from the same patients.Multivariate logistic analysis models were used to compare the pregnancy outcomes between the two groups. Results: In the PGT-A group,293 blastocysts obtained from59patients underwent PGT-A.The proportions of euploidy,aneuploidy and mosaic blastocysts were56.31%,25.60%and18.09%,respectively.A comparison of the euploidy rates of different quality blastocysts showed that the rate of good-quality blastocysts was significantly higher than that of poor-quality blastocysts (67.66% vs 46.88%; odds ratio [OR],2.203;95%confidence interval[CI],0.943–3.612;P=0.002).However,no significant difference was observed in the different developmental rates blastocysts.Compared with Day 5 blastocysts, the euploidy rates of Day 6 and Day 7 blastocysts were not significantly different(61.54%vs51.91%;OR,0.945;95%CI,0.445–2.010;P=0.884;and 61.54%vs47.37%;OR,1.106;95%CI,0.774–1.578;P=0.581,respectively).As for the pregnancy outcomes,the clinical pregnancy rate was significantly increase after the use of PGT-A compared with the control group(71.19%vs56.30%;OR,0.538;95%CI,0.262–1.104;P=0.039).However, the spontaneous abortion rates and ongoing pregnancy rates were not significantly different between the control and PGT-A groups (21.43%vs 19.40%;aOR,0.727;95%CI,0.271–1.945;P=0.525;and55.93%vs45.38%;aOR,0.649;95%CI,0.329–1.283;P = 0.214,respectively). Conclusion: PGT-A improved the clinical pregnancy rate after blastocyst transfer in RIF patients aged under 38 years,but conventional IVF resulted in spontaneous abortion rate and ongoing pregnancy rate that were noninferior to the rates with PGT-A. Key words: recurrent implantation failure, preimplantation genetic testing for aneuploidy, blastocyst, frozen embryo transfer, pregnancy